2003
DOI: 10.1111/j.1348-0421.2003.tb03412.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of the Low pH‐Sensitive Conformational Epitope of Rabies Virus Glycoprotein Recognized by a Monoclonal Antibody #1‐30‐44

Abstract: Monoclonal antibody (mAb) #1‐30‐44 recognized an acid‐sensitive conformational epitope of rabies virus glycoprotein (G). The antigenicity of G protein exposed on the cell surface was lost when the infected cells were exposed to pH 5.8. By comparing the deduced amino acid sequence of G protein between the HEP‐Flury strain and the epitope‐negative CVS strain as well as the mAb‐resistant escape mutants, two distant sites that contained Lys‐202 and Asn‐336 were shown to be involved in the epitope formation. Lys‐20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…2 and Table 1, Gs proteins were recognized by most of our conformational epitope-specific anti-G mAbs except for one mAb, #1-30-44 (Fig. 2, lane 2), the mAb that recognized an acid-sensitive conformational epitope that is formed by two separate regions (Lys-202-containing and Asn-336-containing regions) of G protein (10). These observations indicate that the Gs protein took a 1-30-44-epitope-negative conformation (referred to as the Gc form), while the 1-30-44 epitope-positive conformation (referred to as the G B form) was detected in the authentic G protein (Table 1; 11).…”
Section: Properties Of the Gs Protein Produced In The Virus Infected mentioning
confidence: 86%
See 4 more Smart Citations
“…2 and Table 1, Gs proteins were recognized by most of our conformational epitope-specific anti-G mAbs except for one mAb, #1-30-44 (Fig. 2, lane 2), the mAb that recognized an acid-sensitive conformational epitope that is formed by two separate regions (Lys-202-containing and Asn-336-containing regions) of G protein (10). These observations indicate that the Gs protein took a 1-30-44-epitope-negative conformation (referred to as the Gc form), while the 1-30-44 epitope-positive conformation (referred to as the G B form) was detected in the authentic G protein (Table 1; 11).…”
Section: Properties Of the Gs Protein Produced In The Virus Infected mentioning
confidence: 86%
“…As to the 1-30-44 epitope, we previously reported that at least two amino acids located in two separate regions (i.e., Lys-202 and Asn-336) are involved in the epitope formation (10,11). The Lys-202 is included in the neurotoxin-like region (17), while Asn-336 is located close to Arg-333, substitution of which affects the neurotropic nature of rabies virus in vivo (24,26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations